Chemical and physical observations of particulate matter at Golden Ears Provincial Park from anthropogenic and biogenic sources - Shantz, N. C.; Aklilu, YA; Ivanis, N; Leaitch, W. R.; Brickell, P. C.; Brook, J. R.; Y. Cheng; Halpin, D; Li, S. M.; Tham, YA; Toom-Sauntry, D.; Prenni, A. J.; et al. (ATMOSPHERIC ENVIRONMENT, 2004)
Measurements of a number of aerosol properties and trace gases were conducted at Golden Ears Provincial Park (GE park), near the town of Maple Ridge, B.C., Canada from 6th to 11th of August 2001, just prior to the beginning of the main Pacific 2001 study. The measurements were intended to help with the characterization of the particulate matter (PM) in the forest that borders the northern side of the Lower Fraser Valley (LFV). The concentrations of inorganic ions in the particles decreased after 8th August, while the organic mass concentrations in the particles increased after 8th August. Throughout the study, organic carbon (OC) was the single highest component of the aerosol, and after 8th August, OC comprised about 90% of the particle composition. During the daytime, there was a clear anthropogenic influence from upslope flow driven by the sea breeze. The mixing ratio of monoterpenes increased overnight, when the winds were from the forests to the north but the cis-pinonic acid increased during the day, along with the anthropogenic tracers, suggesting that the oxidation of monoterpenes occurred with the help of anthropogenic oxidants. The particle volume data showed increases often corresponding with decreases in monoterpenes. A steady increase in particle volumes resulted from condensation of OC on the particles, and despite an increase in water soluble organic carbon (WSOC) the effectiveness of the OC at absorbing water for relative humidity (RH) values less than or equal to90% was low relative to sulphate. (C) 2004 Elsevier Ltd. All rights reserved.